Impact of sleep disorders on cerebrovascular diseases - XUE Rong; ZHANG Xuan (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Sleep is an important process for the body to adjust and restore normal physiological functions. Sleep disorders can increase the risk of cerebrovascular diseases. This article reviews the effects of common sleep disorders subtypes on cerebrovascular diseases in order to provide a new target for the prevention and treatment of cerebrovascular diseases.